2015
DOI: 10.2334/josnusd.57.151
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genial tubercle anatomy using cone beam computed tomography

Abstract: The purpose of this study was to characterize the anatomy of the genial tubercle using cone beam computed tomography (CBCT). The morphology and detailed anatomy of the genial tubercle were assessed retrospectively in 201 patients (101 females, 100 males) using CBCT images. The parameters examined were the height (GH) and width (GW) of the genial tubercle, the distance from the lower incisors to the superior border of the tubercle (I-SGT), the distance from the inferior margin of the tubercle to the inferior ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
5
1
Order By: Relevance
“…The mean I-SGT measurement in our study was 8.26 ± 2.7 mm, and a similar result was discussed by Kolsuz et al[17], who studied the anatomy of the genial tubercle using CBCT among a Turkish sample population and found that the mean I-SGT was 8.1 ± 1.7 mm in males and 7.7 ± 1.8 in females with class I occlusion.…”
Section: Discussionsupporting
confidence: 91%
“…The mean I-SGT measurement in our study was 8.26 ± 2.7 mm, and a similar result was discussed by Kolsuz et al[17], who studied the anatomy of the genial tubercle using CBCT among a Turkish sample population and found that the mean I-SGT was 8.1 ± 1.7 mm in males and 7.7 ± 1.8 in females with class I occlusion.…”
Section: Discussionsupporting
confidence: 91%
“…The present data was similar to that found by Kolsuz et al (8.3–10.1 mm). 15 However, it was higher than the measurements found by Araby et al (8.13 ± 3.07 mm) 4 and Wang et al (6.4–8.4 mm). 3 In addition, this distance was significantly greater in males than females and lower in IIA GTs.…”
Section: Discussionmentioning
confidence: 51%
“… 14 The present study proposed a classification system for GTs evaluating their disposition in the mandible, differing from the unique investigation that had classified the GTs in five categories. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CBCT scanning and three-dimensional reconstruction were used in this study. One of the advantages of three-dimensional measurements of the complex structure of the upper airway is that they are more precise and objective 17,18 .…”
Section: Discussionmentioning
confidence: 99%